2006
DOI: 10.1212/01.wnl.0000200956.76449.3f
|View full text |Cite
|
Sign up to set email alerts
|

NCAM is hyposialylated in hereditary inclusion body myopathy due to GNE mutations

Abstract: The authors found that the neural cell adhesion molecule (NCAM) is hyposialylated in hereditary inclusion body myopathy (HIBM) muscle, as suggested by its decreased molecular weight by Western blot. This abnormality represented the only pathologic feature differentiating HIBM due to GNE mutations from other myopathies with similar clinical and pathologic characteristics. If further confirmed in larger series of patients, this may be a useful diagnostic marker of GNE-related HIBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 9 publications
5
59
1
Order By: Relevance
“…Eventually, the Gne M712T/M712T mice may develop myopathic features, if they can be maintained well past weaning. Even very young mutant mice exhibited hyposialylation of PSA-NCAM (i.e., in brain) ( Figure 5D), previously reported in skeletal muscle of HIBM patients (15) and in embryonic stem cells of Gne knockout mice (16).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Eventually, the Gne M712T/M712T mice may develop myopathic features, if they can be maintained well past weaning. Even very young mutant mice exhibited hyposialylation of PSA-NCAM (i.e., in brain) ( Figure 5D), previously reported in skeletal muscle of HIBM patients (15) and in embryonic stem cells of Gne knockout mice (16).…”
Section: Discussionsupporting
confidence: 77%
“…The pathologic mechanism of muscle fiber degeneration in HIBM remains unknown (12)(13)(14)(15)(16)(17)(18). However, evidence suggests that decreased availability of sialic acid in muscle causes hyposialylation of muscle glycoproteins, whether involving glycans in general (12,13), O-linked glycans in particular (14), polysialic acid on neural cell adhesion molecules (PSA-NCAM) (15,16), or specific O-mannosylated glycosyl residues on α-dystroglycan (18).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, counter to earlier assumptions that flux through the sialic acid pathway does not significantly alter the sialylation of individual glycans (2), analysis of two "high-demand" sialoglycans (i.e. polysialylated NCAM (6) and podocalyxin (7)) suggested that fluctuations in the intracellular concentrations of sialic acid and the corresponding supply of CMP-Neu5Ac critically affected their production. In the current report, we used a global cell level approach to investigate whether these two examples were outliers or whether metabolic flux controls the surface display of sialic acid with fine resolution across a wide range of N-linked glycoproteins.…”
mentioning
confidence: 59%
“…7,22 The earliest and the latest recorded age of onset in patients from the Middle East were 17 and 48 years, respectively. 5,17,23,24 The mean onset age of Japanese and Indian patients was 26 years. 5,20 The average onset age in our 18 patients was similar, 25.7 years.…”
Section: Phenotype Spectrum Of Variantsmentioning
confidence: 99%
“…It has been shown that normal sialylation is crucial for the stabilization and function of skeletal muscle glycoproteins and that modifications in the sialylation of cell surface glycoproteins can influence cell adhesion and signal transduction and cause myofibrillar degeneration, resulting in loss of normal muscle function. [16][17][18] Studies have demonstrated that some skeletal muscle proteins, such as neprilysin, 19 alphadystroglycan, 16 O-linked glycans, 20 and neural cell adhesion molecule (NCAM) 17 are hyposialylated in GNE myopathy, a distinctive feature in comparison with other myopathies with similar clinical manifestations. The suggested impact of GNE variants on sialylation remains controversial and under study.…”
Section: Introductionmentioning
confidence: 99%